Ginsenoside Rb1 Alleviates DSS-Induced Ulcerative Colitis by Protecting the Intestinal Barrier Through the Signal Network of VDR, PPARγ and NF-κB - Zhou Y; Xiong X; Cheng Z; Chen Z; Wu S; Yu Y; Liu Y; Chen G; Li L (Dove Medical Press, 2024)
Yi Zhou,1 Xinyu Xiong,1 Zhe Cheng,1 Zekai Chen,1 Shizhen Wu,2 Yan Yu,3 Yujin Liu,4 Guang Chen,1 Lingli Li5 1Department of Integrated Traditional Chinese and Western Medicine, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430030, People's Republic of China; 2College of Acupuncture and Bone Injury, Hubei University of Chinese Medicine, Wuhan, 430061, People's Republic of China; 3Department of Gastroenterology, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430030, People's Republic of China; 4Department of Integrated Traditional Chinese and Western Medicine, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430022, People's Republic of China; 5Department of Traditional Chinese Medicine, Wuhan Fourth Hospital, Wuhan, 430033, People's Republic of ChinaCorrespondence: Lingli Li, Department of Traditional Chinese Medicine, Wuhan Fourth Hospital, Wuhan, 430033, People's Republic of China, Email 379994890@qq.com Guang Chen, Department of Integrated Traditional Chinese and Western Medicine, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430030, People's Republic of China, Email guangchen@tjh.tjmu.edu.cnPurpose: Ginseng (Panax ginseng Meyer) is an herbal medicine used in traditional Chinese medicine (TCM), has the effects of treating colitis and other diseases. Ginsenoside Rb1 (GRb1), a major component of ginseng, modulates autoimmunity and metabolism. However, the mechanism underlying GRb1 treatment of ulcerative colitis (UC) has not yet been elucidated. UC is a refractory inflammatory bowel disease (IBD) with a high recurrence rate, and researches on new drugs for UC have been in the spotlight for a long time.Methods: Mice with DSS-induced UC were treated with GRb1 or 0.9% saline for 10 days. Colon tissue of UC mice was collected to detect the levels of intestinal inflammatory cytokines and integrity of the intestinal barrier. RNA-seq and network pharmacology were used to predict the therapeutic targets of GRb1 during UC treatment.Results: GRb1 treatment alleviated intestinal inflammation and improved intestinal barrier dysfunction in UC mice. Specifically, GRb1 downregulated the levels of pro-inflammatory cytokines such as TNF-α and IL-6, while upregulating the level of the anti-inflammatory cytokine IL-10. Additionally, GRb1 treatment increased the levels of tight junction proteins including ZO-1, Occludin, and E-cadherin, which are crucial for maintaining intestinal barrier integrity. Further analyses using RNA-seq and network pharmacology suggested that these effects might involve the regulation of GRb1 in the signal transduction network of VDR, PPARγ, and NF-κB.Conclusion: The study demonstrated that GRb1 effectively alleviated UC by modulating intestinal inflammation and protecting the integrity of the intestinal barrier through the signal transduction network of VDR, PPARγ, and NF-κB.Keywords: ginsenoside Rb1, ulcerative colitis, intestinal barrier, vitamin D receptor, nuclear factor-kappa B